A Critical Assessment of the Impact of the Domestic Environment on Foreign Policy - Al-Fahad, Fahad A.F.S (Technium EconomiA, 2024)
The domestic environment plays a considerable role in shaping a nation’s foreign policy as it can affect decision-making processes and international relations. However, the extent of such impact remains a subject of debate among policymakers and scholars. In this context, this paper aims to critically assess the influence of domestic factors on foreign policy through the perspectives of two contrasting theories: Pluralism and Elitism. Understanding the intricate relationship between domestic factors and foreign policy is essential in comprehending the driving forces behind a country's international actions and the decision-making processes in foreign policy.